Assembling the tree of life - Cracraft, Joel; Donoghue, Michael J. (OUP E-Books., 2004)
Provides a synthesis of knowledge about the history of life. This work treats the major groups of organisms. It is useful for evolutionary biologists, taxonomists, ecologists interested in biodiversity, and for organismic biologists, botanists, and microbiologists.